Fungi Isolated from litter’s forest of Aka Barayun, Lembah Harau and It’s Phosphate Solubilizing Activity - Rahmi, Nurul; Handayani, Dezi; Hilda Putri, Dwi; Violita, Violita (Jurnal Serambi Biologi, 2023)
One of the essential nutrients for plant growth is phosphate, but just 0.1-0.5% is available for plants to use. This problem can be solved by using chemical fertilizers, but for long run could damages environment. An alternative way for chemical fertilizers is using phosphate solubilizing fungi. Phosphate-solubilizing fungi can be isolated from soil or litter. This study aims to isolated fungi from litter’s forest of Aka Barayun, Lembah Harau, West Sumatra and determine it’s phosphate solubilizing potency. Medium for isolation was Potato Dextrose Agar (PDA) and medium for phosphate solubilizing activity test was solid Pikovskaya medium with source of bound phosphate Ca3(PO4)2. Thirteen fungi were isolated successfully from litter’s forest of Aka Barayun, Lembah Harau, West Sumatra, which are coded SR1-SR13. Based on macroscopic and microscopic morphology, it is known that two isolates belong to the genus Penicillium, two isolates belong to Trichoderma, one isolate of Verticillium, one isolate of Fusarium, two isolates of yeast and two isolates are not yet known. Results of the phosphate solubilizing test showed that only seven isolates were able to solubilize phosphate, they are isolates SR2, SR5, SR6, SR7, SR11, SR 12 and SR 13. Phosphate solubilization index is low and ranges from 0.1 to 0.4.